Answer:
Lonnie is not correct
Step-by-step explanation:
A. No B. No C. Yes I honestly don’t know if that’s 100% right tho
-20, -23, -26 (adding three)
Answer:
468
Step-by-step explanation:
=13[42-6]
=13 (36)
=13×36
=468
Answer:
k > 7
Step-by-step explanation:
Given the inequality statement: 4k - (5 + 3k) > 2
Distribute -1 into (5 + 3k):
4k -5 - 3k > 2
Next, add like terms:
k - 5 > 2
Add 5 to both sides of the inequality:
k - 5 + 5 > 2 + 5
k > 7
Please mark my answers as the Brainliest if you find my explanations helpful :)